IMPLEMENTASI KEBIJAKAN PEMBENTUKAN UNIT PELAKSANA TEKNIS DAERAH PROVINSI TIPE A DI BALAI PENGAWASAN TENAGA KERJA KELAS A DINAS TENAGA KERJA DAN TRANSMIGRASI DAERAH PROVINSI SULAWESI UTARA - Pebri Sandy Kaunang; William ., Areros; Deysi ., Tampongangoy (Sam Ratulangi University, 2021)
This study aims to analyze the implementation of the policy for the establishment of a Type A Provincial Technical Implementation Unit at the Class A Labor Supervision Center of the Regional Manpower and Transmigration Office of North Sulawesi Province. The research was conducted for 2 months, from May to June 2021. The research method used in this study was descriptive method with a qualitative phenomenological approach. Data was collected by means of observation, interviews and documentation. Data analysis uses steps consisting of data reduction, data presentation and conclusion drawing. The results of this research indicate that the UPTD (Class A Labor Supervision Center) has the goal of achieving the policy implementation of the establishment of the UPTD based on the main tasks and functions as well as establishing a cooperative relationship in the implementation of labor services including optimizing the quality of service and community participation required in implementing the policy.